2014
DOI: 10.1016/j.jcpo.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness in practice and its effect on clinical outcomes

Abstract: a b s t r a c tThe value of new cancer drugs is maximized when they are used for the right patient in the right way in clinical practice. Clinical trials conducted during drug development are the most important source of information to predict value at the time a drug is introduced in practice. Regulatory approval is an indication of value, which lately has been complemented with an assessment of clinical value for decisions about reimbursement, using the methodology of health technology assessment (HTA). Form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…However, the healthcare system is not yet prepared for this new role. Although data on use of resources and actual outcomes from specific interventions are rapidly evolving, and methods for comparative effectiveness analysis are being presented, the actual use of such studies is still in an early stage (J€ onsson et al, 2014;Luce et al, 2010). There are many reasons for this.…”
Section: Follow-up Studies Of Costeffectiveness Of New Interventions mentioning
confidence: 99%
“…However, the healthcare system is not yet prepared for this new role. Although data on use of resources and actual outcomes from specific interventions are rapidly evolving, and methods for comparative effectiveness analysis are being presented, the actual use of such studies is still in an early stage (J€ onsson et al, 2014;Luce et al, 2010). There are many reasons for this.…”
Section: Follow-up Studies Of Costeffectiveness Of New Interventions mentioning
confidence: 99%
“…A recent article revealed a strong association between access to (expensive) biologics and the country’s wealth 8. Interestingly, however, another review found that drug coverage for innovative and expensive drugs does not necessarily translate into its use; there were differences in use between countries with comparable reimbursement criteria, and also between regions within a country 9. Differences in attitudes among clinicians likely contribute to differences in treatment choices 10…”
Section: Introductionmentioning
confidence: 99%
“…38 Relative differences in parameter estimates of ≥10% were considered as indicating relevant bias. 39 Regression analyses were estimated in Stata 12. 40 …”
Section: Discussionmentioning
confidence: 99%
“…35,36 Only a few contextual factors, namely gender, 37 education, [38][39][40] socioeconomic status, 39 or coping and helplessness as personal factors, 41 have been studied with regards to their influence on (a limited number of) outcomes. They have shown to contribute importantly to the outcomes studied.…”
Section: Framework For Health or Health Outcomes That Include Contexmentioning
confidence: 99%
See 1 more Smart Citation